Study of pozzolanic properties of two sugarcane bagasse ash samples from Honduras - Bonilla, Mercedes (2016)
It is well known that the combustion of agricultural waste such as rice husk, bamboo leaf and bagasse among others, depending on the combustion process, may produce powders with pozzolanic properties. Two samples of sugarcane bagasse ash (SCBA) from Honduras were studied (from Ingenio Santa Matilde, close to the city of San Pedro Sula, and from Ingenio Los Mangos, close to the city of Choluteca). The samples were physico-chemically characterized and pozzolanic reactivity was checked. Both samples of ash have a chemical composition comprising mainly oxides of silicon, iron and aluminum and have similar values of the loss on ignition. Both ashes showed high ability for reacting towards hydrated lime. Moreover, the evolution of the mechanical compressive strength of mortar specimens incorporating these ashes (25% replacement of Portland cement by SCBA) was also studied. Compressive behavior revealed that for this dosage, the cementing efficiency of SCBA is similar to Portland cement. The results suggested that ashes from San Pedro Sula and Choluteca have very good pozzolanic properties. The cement and concrete industries in Honduras have a huge chance for reusing this type of waste in high quality construction materials.